Indigenous and Native American Authors and Creatives ... - UT Libraries (The University of Texas at Austin, 2022)
Background: The University of Texas Libraries promoted collections through curated selections featured in the main library discovery interface, encouraging visitors to continue to explore these topics by searching the entire collection and checking back each term to find new selections. This snapshot of one of those Featured Collections includes a screenshot of the online display and a list of the selected titles. Featured Collection Description: In recognition of Indigenous Peoples' Day and Native American Heritage Month, we're highlighting a a curated selection of works by Indigenous and Native American authors and creatives, including books, dissertations, essays, and more by UT Longhorns. ...